90Y-clivatuzumab tetraxetan with or without low-dose gemcitabine: A phase Ib study in patients with metastatic pancreatic cancer after two or more prior therapies. Issue 14 (September 2015) - Picozzi, Vincent J.; Ramanathan, Ramesh K.; Lowery, Maeve A.; Ocean, Allyson J.; Mitchel, Edith P.; O'Neil, Bert H.; Guarino, Michael J.; Conkling, Paul R.; Cohen, Steven J.; Bahary, Nathan; Frank, Richard C.; Dragovich, Tomislav; et al.
Abstract: Background: For patients with metastatic pancreatic adenocarcinoma, there are no approved or established treatments beyond the 2nd line. A Phase Ib study of fractionated radioimmunotherapy was undertaken in this setting, administering 90 Y-clivatuzumab tetraxetan (yttrium-90-radiolabelled humanised antibody targeting pancreatic adenocarcinoma mucin) with or without low radiosensitising doses of gemcitabine. Methods: Fifty-eight patients with three (2–7) median prior treatments were treated on Arm A ( N = 29, 90 Y-clivatuzumab tetraxetan, weekly 6.5 mCi/m 2 doses × 3, plus gemcitabine, weekly 200 mg/m 2 doses × 4 starting 1 week earlier) or Arm B ( N = 29, 90 Y-clivatuzumab tetraxetan alone, weekly 6.5 mCi/m 2 doses × 3), repeating cycles after 4-week delays. Safety was the primary endpoint; efficacy was also evaluated. Results: Cytopaenias (predominantly transient thrombocytopenia) were the only significant toxicities. Fifty-three patients (27 Arm A, 26 Arm B, 91% overall) completed ⩾1 full treatment cycles, with 23 (12 Arm A, 11 Arm B; 40%) receiving multiple cycles, including seven (6 Arm A, 1 Arm B; 12%) given 3–9 cycles. Two patients in Arm A had partial responses by RECIST criteria. Kaplan–Meier overall survival (OS) appeared improved in Arm A versus B (hazard ratio [HR] 0.55, 95% CI: 0.29–0.86; P = 0.017, log-rank) and the median OS for Arm A versus Arm B increased to 7.9 versus 3.4 months with multiple cycles (HR 0.32, P = 0.004), including three patients in Arm A surviving >1 year. Conclusions: Clinical studies of 90 Y-clivatuzumab tetraxetan combined with low-dose gemcitabine appear feasible in metastatic pancreatic cancer patients beyond 2nd line and a Phase III trial of this combination is now underway in this setting.